The Role Of Queue In Improving Service Time For Health Clinics - الشيخ حسن, فداء; العلي, مجد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed to investigate the role of using queue models in improving the service time of health clinics in the Syrian Arab Republic. To achieve this goal, the queue model was formulated and resolved using the QM windows program and the study was applied at the cardiac clinic in Tishreen hospital in Damascus during the period from 1/7 to 30/8 of 2019. The study presented an alternative model to improve the current situation in the health clinic. The alternative model significantly improved performance measures. The application of this model also reduces the number of patients in the clinic waiting line to almost zero level.